PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, PENGALAMAN KERJA DAN MOTIVASI KERJA TERHADAP KOMITMEN AFEKTIF GURU DI SMK NEGERI KOTA BINJAI - Pitriani Pitriani Nasution (Hijri, 2018)
This study aimed to determine: (1) the effect perception of transformational leadership style against of work motivation; (2) the effect of work experience of work motivation; (3) the effect perception of transformational leadership style against of commitment affective; (4) the effect work experience of commitment affective; and (5) the effect motivation work of commitment affective. The subject of research is the teachers SMK negeri Kota Binjai with a proportional random sampling of 110 people. Sampling was conducted with a total sampling. Path analysis research method is aimed to test the theory and to obtain information about the study. Based on hypothesis testing can be concluded: (1) there is a direct effect perception of transformational leadership style against of work motivation by tcount ρ31>ttabel α = 5% (2,72 > 1.64); (2) there is a direct effect work experience of work motivation by tcount ρ32>ttabel α = 5% (3,72 > 1.64); (3) there is a direct effect perception of transformational leadership style against of commitment affective by tcount ρ41>ttabel α = 5% (2,32 > 1.64); (4) there is a direct effect work experience of commitment affective by tcount ρ42>ttabel α = 5% (2,72 > 1.64); and (5) there is a direct effect motivation work of commitment affective by tcount ρ43>ttabel α = 5% (1,93 > 1.64). The results provide an overview of the of transformational leadership style the head of school, work experience and motivation of working against the commitment affective the morale of the remaining 33.1 % and other specified circumstances. Keywords: Transformational leadership style is the principal, work experience, work motivation, affective commitment of teachers